Impurity distribution during growth of silicon single crystals for solar cells - Головко, Юрий Викторович (Eastern-European Journal of Enterprise Technologies, 2013)
The article represents the experimental data on the study of the distribution of the main impurities between the liquid and solid phases in the course of growing of the silicon single crystal by the Czochralski method. The mathematical models of the distribution of boron, oxygen, carbon impurities, based on the balance equation of the impurity atoms at each moment of growing, were presented. The main advantage of the developed models is the fact that in their construction, the effective distribution coefficient of impurities is considered as a function of the crystallized fraction of the melt, which is a proxy indicator of the whole complex of technological factors, which vary throughout the process of growing of a single crystal. In addition they do not use physical parameters that can not be measured in specific industrial environments. The suggested models permit to determine the real effective coefficients of distribution of the main impurities, according to the data of the standard quality control of silicon single crystal. The models are used to determine, according to the experimental data of the impurity concentration in the silicon single crystal with a crystalographic orientation <100> and the diameter 100 mm, the values of the effective coefficients of distribution of impurities of boron, oxygen, carbon, at various stages of growing.